Engineering polyamide materials: s-triazine framework with specialized bulky side chains for advanced applications - Bhalani, Deep; Pathan, Sabir Khan; V.Modh, Jignasa (Mongolian Journal of Chemistry, 2024)
The focus of this study is on the synthesis of organic fluorescent and thermally stable polyamides using an s-triazine frame. Coumarin and n-phenyl anthranilic acid have been utilized as bulky pendent groups in the synthesis of the monomer, resulting in polyamides with two groups that enhance stability and fluorescence. The synthesized polyamides have been characterized using a variety of techniques. The thermal stability of the polyamides has been studied using thermogravimetric analysis. These polyamides offer appealing features such as fluorescence and enhanced thermal stability, making them significant for a wide range of applications, including biosensors, clean energy technologies, and explosive sensing.